Educational Researchers and the Regional University 2019
DOI: 10.1007/978-981-13-6378-8_5
|View full text |Cite
|
Sign up to set email alerts
|

An Invited Outsider or an Enriched Insider? Challenging Contextual Knowledge as a Critical Friend Researcher

Abstract: Researchers conducting studies in communities have long taken an interest in exploring the different merits of positioning themselves as 'insiders', 'outsiders' or 'inbetweeners' in relation to their participants. Yet research exploring the role of the researcher as a 'critical friend' --a supportive yet challenging facilitator in self-evaluation processes-has not been fully examined. This chapter speaks to the FUGuE element of transformation, which in the present context I define as a process where structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…This would suggest that PLC colleagues need to perceive that 'why' considerations that set the direction of the PLC's work need to be of importance, or else the process of working to realise possibilities will go nowhere. The specific content in a PLC cannot be imposed by outsiders (Banks, 1998;Fletcher, 2019), but is created by those who share questions, concerns, problems and needs (Woods & Macfarlane, 2017). A PLC is also characterised by mutual engagement in procedures, tools, con cepts and different ways of acting, i.e., a shared repertoire to illuminate 'why' as well as 'how' questions (cf.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would suggest that PLC colleagues need to perceive that 'why' considerations that set the direction of the PLC's work need to be of importance, or else the process of working to realise possibilities will go nowhere. The specific content in a PLC cannot be imposed by outsiders (Banks, 1998;Fletcher, 2019), but is created by those who share questions, concerns, problems and needs (Woods & Macfarlane, 2017). A PLC is also characterised by mutual engagement in procedures, tools, con cepts and different ways of acting, i.e., a shared repertoire to illuminate 'why' as well as 'how' questions (cf.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…For example, Banks (1998) presents a crosscultural framework to understand community which includes values, perspectives, behaviours, beliefs and knowledge as its defining points. A recent adap tion of Banks' framework incorporates features of effective learning communities (Coates, 2017;Woods & Macfarlane, 2017), in which a PLC's common reference points relate to shared vision, values, culture and ethos (Fletcher, 2019). The term 'vision' refers to those common ideals and goals the PLC aspires to achieve.…”
Section: Plc Identitymentioning
confidence: 99%
“…Pine (2009) suggests that such a knowledge claim can be accomplished through a reconceptualisation of action research as a form of professional development with critical friends. Over time, rigorous procedures for incorporating critical friends into action research have been suggested in the literature (see Fletcher, 2019;Franzak, 2002;Swaffield, 2008)…”
Section: The Needs Of Critical Friendsmentioning
confidence: 99%
“…An external-outsider is not a member of the community, whereas an indigenous-outsider is rejected as a legitimate community member despite being socialised within its culture. Fletcher (2019) refers to these group membership categories as different types of ‘critical friendships’ distinguishable by the level of imposing, proposing and/ or sharing of the researcher’s friendship in relation to research participants.…”
Section: What Does It Mean To Be An ‘Insider’?mentioning
confidence: 99%